CFD simulations of hydraulic short-circuits in junctions, application to the Grand'Maison power plant. Issue 1 (1st September 2022) - Decaix, J; Drommi, J-L; Avellan, F; Münch-Alligné, C
Abstract: In the framework of the XFLEX HYDRO H2020 European Project, the pumped-storage power plant of Grand'Maison (France), owned by Electricité De France, focuses on the implementation of the hydraulic short-circuit (HSC) operating mode. This mode increases the flexibility in pumping mode, which helps the integration of intermittent energies. Grand'Maison is divided into two power houses: the first features four Pelton turbine units and the second eight reversible pump-turbines units. A trifurcation splits the flow into three penstocks, each is then split into two branches that feed each power house. The HSC operating mode, which consists in operating the pumps and the Pelton turbines simultaneously, changes the flow paths in the junctions compared to the pump mode. The power plant was not designed to operate in HSC mode over a long duration, therefore an assessment of its feasibility is necessary. 151 computational fluid dynamic simulations are carried out for two bifurcations and one trifurcation. The numerical simulation results show that the local head losses in HSC mode represent less than 1% of the gross head. No flow instabilities are observed at the bifurcations contrary to the trifurcation. Additional analyses are required to better understand the flow in the trifurcation.